Homogeneity of Memory Errors in Abstract Visual Pattern Recall - Stephen P. Badham; Christopher Atkin; Antonio Castro (Europe's Journal of Psychology, 2019)
In memory tests, recalled information can be distorted by errors in memory and these distortions can be more memorable than the original stimuli to a later learner. This is typically observed over several generations of learners but there is less exploration of the initial distortions from the first generation of learners. In this article, participants studied visual matrix patterns which were either erroneous recall attempts from previous participants or were random patterns. Experiment 1 showed some evidence that material based on previous participants’ recall data was more memorable than random material, but this did not replicate in Experiment 2. Of greater interest in the current data were homogeneity in the memory errors made by participants which demonstrated systematic recall biases in a single generation of learners. Unlike studies utilising multiple generations of learners, the currently observed distortions cannot be attributed to survival-of-the-fittest mechanisms where biases are driven by encoding effects.